Neonatal and pediatric pharmacology : therapeutic principles in practice - Yaffe, Sumner J., 1923-; Aranda, Jacob V. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2010)
"Neonatal and Pediatric Pharmacology offers guidelines for safe, effective, and rational drug therapy in newborns, children and adolescents. The book provides relevant and useful data on the molecular, physiologic, biochemical, and pharmacologic mechanisms of drug action and therapy in this population. The authors identify areas of innovative basic and translational research necessary for the continuing evaluation and development of drugs for the fetus, newborns, children and adolescents. Neonatal and Pediatric Pharmacology is is a valuable reference for all health care professionals who treat the fetus, newborns, children, and adolescents, including neonatologists, nurses, pediatricians, general practitioners, students, obstetricians, perinatologists, surgeons and allied health professionals. It will be useful anytime during the day and especially in the middle of the night when knowledge of appropriate indications, safe and effective use, dosage, and therapeutic regimen for a certain drug or molecular entity is immediately needed. The book is also directed to those involved in basic, clinical, and other academic pharmacological research, the pharmaceutical industry, and regulatory agencies dealing with drug and therapeutic developments for this population. Those teaching pharmacology and therapeutics will find this compilation of information extremely useful in preparing teaching materials"--Provided by publisher.